2004
DOI: 10.1016/j.physa.2004.04.073
|View full text |Cite
|
Sign up to set email alerts
|

A heavenly example of scale-free networks and self-organized criticality

Abstract: The sun provides an explosive, heavenly example of self-organized criticality. Sudden bursts of intense radiation emanate from rapid rearrangements of the magnetic field network in the corona. Avalanches are triggered by loops of flux that reconnect or snap into lower energy configurations when they are overly stressed. Our recent analysis of observational data reveals that the loops (links) and footpoints (nodes), where they attach on the photosphere, embody a scale free network. The statistics of the avalanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
(9 reference statements)
0
19
0
Order By: Relevance
“…These bursts can reach sufficiently high energies to pose a risk to astronauts, spacecraft, or airplanes following polar routes. In addition they exhibit a number of empirical features associated with SOC [9,15,16,17,18,19]. For instance, the distribution of event durations and quiet times is a power-law for both solar flux and the BTW sandpile [9], once physically relevant detection thresholds are taken into account to compare these time series on an equal basis.…”
Section: Solar X-ray Fluxmentioning
confidence: 99%
“…These bursts can reach sufficiently high energies to pose a risk to astronauts, spacecraft, or airplanes following polar routes. In addition they exhibit a number of empirical features associated with SOC [9,15,16,17,18,19]. For instance, the distribution of event durations and quiet times is a power-law for both solar flux and the BTW sandpile [9], once physically relevant detection thresholds are taken into account to compare these time series on an equal basis.…”
Section: Solar X-ray Fluxmentioning
confidence: 99%
“…It is convenient to quote the seminal work by Voss and Clarke [5]. These authors have found in fact that music composition yields a 1/f noise spectrum, which is generally regarded as a complexity manifestation [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of magnetic concentration sizes on the photosphere is also scale invariant, and the coronal magnetic network embodies a scale-free network [4,5]. In fact, a model of self-organized criticality (SOC) with avalanches of reconnecting flux tubes reproduces the observed scale-free network structure [4,6].As part of the debate on the characterization of magnetohydrodynamic turbulence in this regime [1,4,5,6,7,8,9], interest has focused on comparing interoccurrence times between flares with those in models of SOC. Analyses of flare catalogs have indicated scale invariance of the waiting times, but the behavior was found to vary with the phase of the solar cycle [10] and with the methods used to analyze the catalogs.…”
mentioning
confidence: 99%